Integration of Transcriptomics and Metabolomics Reveals Mechanisms of High-Temperature Stress Tolerance in the Hepatopancreas of Penaeus monodon - Li Liu; Peng Zhao; Lishi Yang; Yundong Li; Zhong Huang; Qibin Yang; Yukai Yang; Jianzhi Shi; Yibiao Chen; Jianhua Huang (Biology)
High temperatures in summer often trigger disease outbreaks in shrimp, resulting in significant economic losses. To investigate the heat tolerance mechanisms of Penaeus monodon, juvenile tiger shrimp were subjected to a high-temperature stress of 38 °C for 144 h. The cumulative survival rate of shrimp sharply decreased to 5.29% in the later 144 h. The heat-sensitive shrimps (S group) were collected in the first 24 h, while those that survived beyond 120 h were collected as the heat-tolerant group (T group). The hepatopancreas of two groups was subjected to transcriptomic and metabolomic analysis. The results revealed that, compared to the S group, the T group exhibited a total of 3527 DEGs, including 2199 upregulated and 1328 downregulated genes. Additionally, 353 DAMs were identified in the T group, with 75 metabolites showing increased levels and 278 metabolites displaying decreased levels. The results revealed that the mechanisms of heat tolerance involve energy supply strategies, immune system regulation, amino acid metabolism, and glutathione metabolism. Energy supply strategies include the digestion and absorption of carbohydrates and proteins, glycolysis/gluconeogenesis, fructose and mannose metabolism, and pyruvate metabolism, all of which collectively meet energy demands in high-temperature environments. The immune system is regulated by C-type lectin receptor pathways and IL-17 signaling pathways, which together coordinate innate immunity to prevent pathogen invasion. In amino acid metabolism, various glycogenic amino acids, such as histidine, phenylalanine, valine, and serine, are metabolized for energy, while excess ammonia is converted to γ-glutamyl-glutamate and L-glutamate to mitigate ammonia accumulation. Combined transcriptomic and metabolomic analyses further indicate that glutathione metabolism plays a crucial role in the adaptation of P. monodon to high-temperature environments. This study explains the high-temperature tolerance mechanism of P. monodon from the aspects of gene expression regulation and material metabolism regulation and also provides a scientific basis and basic data for the selection and breeding of new varieties of P. monodon with a high-temperature tolerance.